Supervised disulfiram treatment in patients with alcohol dependence - Yargıç, L. İlhan and Soleimanvandi, Habib (Journal of Dependence, 2005)
Objective: Main difficulty during disulfiram therapy in alcohol dependence is that the patients quit taking their medication after a while if they are taking it on their own. This study aims to observe the treatment compliance and length of abstinence in patients taking disulfiram under supervision. Method: This study presents the treatment follow-up of 38 alcohol dependent patients who were recommended to take disulfiram 500 mg/day under the supervision of a significant other. Their compliance and abstinence durations were observed. Results: 27 patients continued the treatment after they accepted supervised disulfiram therapy. The mean duration of follow up of these patients was 109 days (min: 20 days, max: 1 year). 11 patients reported that they tried taking alcohol while they were on disulfiram. Disulfiram was discontinued in one patient because of repeated alcohol use while taking this medication. Medication was discontinued because of organic brain syndrome in 5 patients and because of muscle weakness in 2 patients. In 3 of the patients who stopped taking disulfiram due to adverse effects, this medication was restarted at a lower dose (250 mg/day) after the adverse symptoms subsided. 9 patients took disulfiram regularly as recommended. A mean of 6 months (min: 2 months, max: 1 year) of abstinence was provided in these patients. Conclusion: These findings suggest that supervised disulfiram therapy should be in the treatment menu in the treatment of alcohol dependence for suitable patients.